Recovery of the Decreased Phagocytic Function of Peripheral Monocytes and Neutrophil Granulocytes following Cytoreductive Surgery in Advanced Stage Epithelial Ovarian Cancer - Anna Rebeka Kovács; Luca Lukács; László Pál; Sándor Szűcs; Kincső Sára Kovács; Rudolf Lampé (Medicina, 2023)
(1) Monocytes and neutrophil granulocytes are the phagocytic cells of the innate immune system, playing a crucial role in recognizing and eliminating tumor-transformed cells. Our objective was to assess the impact of advanced-stage epithelial ovarian cancer (EOC) and cytoreductive surgery on the phagocytic function of peripheral monocytes and neutrophil granulocytes. We aimed to compare the pre- and postoperative phagocytic function of these immune cells in EOC patients with healthy control women. Additionally, we aimed to examine the influence of surgery on phagocytic function by comparing pre- and postoperative samples from patients with benign gynecological tumors. (2) We examined peripheral blood samples from 20 patients with FIGO IIIC stage high-grade serous EOC and 16 patients with benign gynecological tumors as surgical controls, collected before and seven days after tumor removal surgery, and from 14 healthy women. After separation, the cells were incubated with Zymosan-A particles, and the phagocytic index (PI) was assessed using immunofluorescence microscopy. One-way ANOVA, the Kruskal–Wallis H-test, and the paired samples t-test were used for the statistical analysis of the data. A significance level of p < 0.05 was applied. (3) Peripheral monocytes and neutrophils from EOC patients exhibited significantly lower preoperative PI values compared to healthy controls (p < 0.001; p < 0.001, respectively). Following cytoreductive surgery, the PI values of immune cells in EOC patients significantly increased by the 7th postoperative day (p < 0.001; p < 0.001), reaching levels comparable to those of healthy controls (p = 0.700 and p = 0.991). In contrast, there was no significant disparity in the PI values of cells obtained from pre- and postoperative blood samples of surgical controls when compared to healthy women (monocytes: p = 0.361 and p = 0.303; neutrophils: p = 0.150 and p = 0.235). (4) EOC and/or its microenvironment may produce factors that reduce the phagocytic function of monocytes and neutrophils, and the production of these factors may be reduced or eliminated after tumor removal.